Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Northwestern University's Program of African Studies, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found